Extracorporeal membrane oxygenation support for lung transplantation: Initial experience in a single center in China and a literature review - Zhao, Yanfeng; Su, Yiliang; Duan, Ruowang; Song, Jiong; Liu, Xiaogang; Shen, Lei; Ding, Junrong; Zhang, Pei; Bao, Minwei; Chen, Chang; Zhu, Yuming; Jiang, Gening; et al. (Frontiers in Medicine, 2022)
Background: Extracorporeal membrane oxygenation (ECMO) is a versatile tool associated with favorable outcomes in the field of lung transplantation (LTx). Here, the clinical outcomes and complications of patients who underwent LTx with ECMO support, mainly prophylactically both intraoperatively and postoperatively, in a single center in China are reviewed. Methods: The study cohort included all consecutive patients who underwent LTx between January 2020 and January 2022. Demographics and LTx data were retrospectively reviewed. Perioperative results, including complications and survival outcomes, were assessed. Results: Of 86 patients included in the study, 32 received ECMO support, including 21 who received prophylactic intraoperative use of ECMO with or without prolonged postoperative use (pro-ECMO group), while the remaining 54 (62.8%) received no external support (non-ECMO group). There were no significant differences in the incidence of grade 3 primary graft dysfunction (PGD), short-term survival, or perioperative outcomes and complications between the non-ECMO and pro-ECMO groups. However, the estimated 1- and 2-year survival were superior in the pro-ECMO group, although this difference was not statistically significant (64.1% vs. 82.4%, log-rank p = 0.152; 46.5% vs. 72.1%, log-rank p = 0.182, respectively). After regrouping based on the reason for ECMO support, 30-day survival was satisfactory, while 90-day survival was poor in patients who received ECMO as a bridge to transplantation. However, prophylactic intraoperative use of ECMO and postoperative ECMO prolongation demonstrated promising survival and acceptable complication rates. In particular, patients who initially received venovenous (VV) ECMO intraoperatively with the same configuration postoperatively achieved excellent outcomes. The use of ECMO to salvage a graft affected by severe PGD also achieved acceptable survival in the rescue group. Conclusions: Prophylactic intraoperative ECMO support and postoperative ECMO prolongation demonstrated promising survival outcomes and acceptable complications in LTx patients. Particularly, VV ECMO provided safe and effective support intraoperatively and prophylactic prolongation reduced the incidence of PGD in selected patients. However, since this study was conducted in a relatively low-volume transplant center, further studies are needed to validate the results.